Peningkatan Potensi Diri: Mengenali Diri, Minat, dan Bakat pada Pelajar SMK - Ira Hasianna Rambe; Yoko Jimmy Panjaitan; Myrna Anissaniwaty; Linda Widyastuti (BADAN PENERBIT STIEPARI PRESS, 2023)
Adolescence is a period often marked by a crisis of self-identity. During this time, individuals typically find it challenging to discover their identity based on their talents, interests, and skills. Vocational schools are one option for acquiring specific skills after graduation. However, not everything goes as planned. It is evident that many vocational school graduates, after completing their education, either work in a field unrelated to their vocational training or pursue a different major in higher education. This phenomenon is also observed at Pasundan Rancaekek Vocational School. The method employed to achieve the goals of this community service program involves thorough preparation and coordination with partners during implementation, as well as evaluating the success of the program. The objective of this activity is to enhance students' knowledge about their interests and talents, enabling them to make informed decisions about their majors and careers. The target of this activity is for students to be able to identify their talents and interests.